Modulation of FLT3 signal transduction through cytoplasmic cysteine residues indicates the potential for redox regulation - Böhmer, Annette; Barz, Saskia; Schwab, Katjana; Kolbe, Ulrike; Gabel, Anke; Kirkpatrick, Joanna; Ohlenschläger, Oliver; Görlach, Matthias; Böhmer, Frank-D. (Redox biology, 2020)
Oxidative modification of cysteine residues has been shown to regulate the activity of several protein-tyrosine kinases. We explored the possibility that Fms-like tyrosine kinase 3 (FLT3), a hematopoietic receptor-tyrosine kinase, is subject to this type of regulation. An underlying rationale was that the FLT3 gene is frequently mutated in Acute Myeloid Leukemia patients, and resulting oncogenic variants of FLT3 with ‘internal tandem duplications (FLT3ITD)’ drive production of reactive oxygen in leukemic cells. FLT3 was moderately activated by treatment of intact cells with hydrogen peroxide. Conversely, FLT3ITD signaling was attenuated by cell treatments with agents inhibiting formation of reactive oxygen species. FLT3 and FLT3ITD incorporated DCP-Bio1, a reagent specifically reacting with sulfenic acid residues. Mutation of FLT3ITD cysteines 695 and 790 reduced DCP-Bio1 incorporation, suggesting that these sites are subject to oxidative modification. Functional characterization of individual FLT3ITD cysteine-to-serine mutants of all 8 cytoplasmic cysteines revealed phenotypes in kinase activity, signal transduction and cell transformation. Replacement of cysteines 681, 694, 695, 807, 925, and 945 attenuated signaling and blocked FLT3ITD-mediated cell transformation, whereas mutation of cysteine 790 enhanced activity of both FLT3ITD and wild-type FLT3. These effects were not related to altered FLT3ITD dimerization, but likely caused by changed intramolecular interactions. The findings identify the functional relevance of all cytoplasmic FLT3ITD cysteines, and indicate the potential for redox regulation of this clinically important oncoprotein. [Display omitted] •Fms-like tyrosine kinase 3 (FLT3) can be activated in intact cells by exposure to hydrogen peroxide.•Signaling of the oncoprotein FLT3ITD (FLT3 with internal tandem duplication) can be attenuated with antioxidants.•FLT3ITD is oxidized at cytoplasmic cysteine residues 695 and 790.•The FLT3ITD cytoplasmic cysteine residues 681, 694, 695, 807, 925, and 945 are essential for cell transformation.•Replacement of cysteine 790 with serine causes FLT3 activation.•The findings indicate the potential of FLT3/FLT3ITD redox regulation through cytoplasmic cysteine residues.